PUSAT PENELITIAN DAN PENGEMBENGAN TANAMAN PADI DI KABUPATEN BARITO KUALA - Khollis, Ilham Nur; Tharziansyah, Muhammad (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
The Center for Rice Research and Development in Barito Kuala Regency is Kuala a place to conduct research on rice plants and the application of rice farming processes to get quality rice seeds. WithThe problem is